2018
DOI: 10.1021/acs.jafc.8b02557
|View full text |Cite
|
Sign up to set email alerts
|

In Ovo Feeding of Creatine Pyruvate Increases the Glycolysis Pathway, Glucose Transporter Gene Expression, and AMPK Phosphorylation in Breast Muscle of Neonatal Broilers

Abstract: This study aims to investigate in ovo feeding (IOF) of creatine pyruvate (CrPyr) on glucose metabolism, hormone concentration, and the 5'-AMP-activated protein kinase (AMPK) pathway in breast muscle of embryos and neonatal broilers. The three treatments were noninjected control, 0.75% NaCl treatment, and 12 mg CrPyr/egg treatment. The solution was injected on the 17.5 day of incubation. At hatch, 120 male broilers from each treatment were chosen for a 7 day feeding trial. Compared with other treatments, CrPyr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Creatine kinase and phosphocreatine are extremely efficient energy-buffering systems in cells . Once in the cell, creatine is phosphorylated to phosphocreatine by creatine kinase and functions to buffer changes in ATP during the altered energy status. ,, Several studies carried out in humans found that creatine supplementation increased the total creatine pool in the muscle and plasma. ,, The present study showed that CMH supplementation led to higher concentrations of creatine in longissimus dorsi muscle and liver and elevated concentrations of phosphocreatine in longissimus dorsi and semitendinosus muscle of pigs, which was in agreement with the previous studies. Additionally, we also found that dietary GAA induced similar functions to increase the concentrations of creatine and phosphocreatine in the muscle and liver of pigs, which implied that GAA could be absorbed in the intestines and methylated to form creatine, playing an effect similar to CMH. Consistent with the current study, several studies indicated that GAA diets significantly increased the concentrations of creatine in the skeletal muscle of pigs and humans. , …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Creatine kinase and phosphocreatine are extremely efficient energy-buffering systems in cells . Once in the cell, creatine is phosphorylated to phosphocreatine by creatine kinase and functions to buffer changes in ATP during the altered energy status. ,, Several studies carried out in humans found that creatine supplementation increased the total creatine pool in the muscle and plasma. ,, The present study showed that CMH supplementation led to higher concentrations of creatine in longissimus dorsi muscle and liver and elevated concentrations of phosphocreatine in longissimus dorsi and semitendinosus muscle of pigs, which was in agreement with the previous studies. Additionally, we also found that dietary GAA induced similar functions to increase the concentrations of creatine and phosphocreatine in the muscle and liver of pigs, which implied that GAA could be absorbed in the intestines and methylated to form creatine, playing an effect similar to CMH. Consistent with the current study, several studies indicated that GAA diets significantly increased the concentrations of creatine in the skeletal muscle of pigs and humans. , …”
Section: Discussionsupporting
confidence: 56%
“…1 Once in the cell, creatine is phosphorylated to phosphocreatine by creatine kinase and functions to buffer changes in ATP during the altered energy status. 6,46,47 Several studies carried out in humans found that creatine supplementation increased the total creatine pool in the muscle and plasma. 8,9,41 The present study showed that CMH supplementation led to higher concentrations of creatine in longissimus dorsi muscle and liver and elevated concentrations of phosphocreatine in longissimus dorsi and semitendinosus muscle of pigs, which was in agreement with the previous studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Pyruvate, an intermediate metabolite of the gluconeogenesis pathway, plays an important role in energy metabolism [36], and is the end product of glycolysis and the starting substrate for the tricarboxylic acid (TCA) cycle [37]. Previous studies showed that creatine pyruvate improved the energy status, increased the gene expression of glucose transporter proteins, and facilitated glycolysis in breast muscle [38]. In the present study, succinic acid, pyruvic aldehyde and 2isopropylmalic acid were involved in the pyruvate metabolic pathway.…”
Section: Discussionmentioning
confidence: 57%
“…The embryo begins to take in amniotic fluid on the 17th day of embryonic age which is suitable for in ovo feeding. The nutrients are injected into the amniotic cavity of the chicken embryo and then absorbed by the intestine through embryo swallowing ( Zhao et al, 2018 ; Zhang et al, 2020a ). Although the development of the intestine is a precise and orderly process, the function of the intestine can only begin to develop after the embryo swallows amniotic fluid in the late incubation stage ( Wang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%